Interactive Fan Charts: A Space-Saving Technique for Genealogical Graph Exploration - Draper, Geoffrey M.; Riesenfeld, Richard F. (FHTW'08: Proceedings of the Workshop on Technology for Family History and Genealogical Research, 2008)
Fan charts are a popular method for displaying family trees in a compact way. We extend the concept of fan charts to include a number of interactive metaphors, thus transforming what was a static display medium into an interactive tool for browsing and editing genealogical data.